Effects of Primary Chemotherapy, Radiotherapy plus Local Treatments on Regression Patterns of Posterior Pole Retinoblastoma - Naima Zaheer, Nusrat Sharif, Darakhshanda Khurram (Pakistan Journal of Ophthalmology, 2018)
Purpose: To document the types of regression patterns of intraocular retinoblastoma following primary chemotherapy, radiotherapy and local treatments. Material and Methods: The medical records of 31 patients diagnosed with intraocular posterior pole retinoblastoma at the Department of Paediatric Ophthalmology Al-Shifa Trust, Eye Hospital, Rawalpindi between January 2006 and January 2010 were reviewed retrospectively. The size of the tumour before and after the treatment (with chemotherapy, radiotherapy and local therapy) and types of regression patterns were evaluated. Regression patterns were classified as type 0 (no residua), type 1 (fully calcified residua), type 2 (non calcified residua), type 3 (partially calcified), type 4 (flat scar). Cases were also observed for any relapse of tumour. Results: 37 eyes of 31 children were included in the study. Out of which 6 (19.4 %) had bilateral presentation of posterior pole retinoblastoma and 25 (80.6%) had unilateral. Tumour size, location and groupings were noted according to the International Intraocular retinoblastoma classification. After treatment with chemotherapy, radiotherapy and local treatments the types of regressions noted were type 0 in 1 eye (2.7 %), type 1 in 2 eyes (5.4 %), type 2 in 7 eyes (18.9 %), type 3 in 19 eyes (51.3 %) and type 4 in 8 eyes (21.6 %). In 3 eyes tumour relapse occurred. Conclusion: Most large intraocular tumours showed type 3 regression pattern. Small tumours resulted in flat atrophic scars.